50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3631
|View full text |Cite
|
Sign up to set email alerts
|

RANS Simulations for Sensitivity Analysis of Compressor Transition Duct

Abstract: This paper presents a numerical investigation of a strutted annular transition duct used to connect the low pressure and high pressure compressors of aircraft gas turbine engine. Data was generated for one-and six-strut configurations with the United Technologies (UTC) flow solver. For reference, some cases were also run with the ANSYS FLUENT software package. The validity of the computed velocity and pressure loading distributions was established with the existing experimental data available in the open liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(12 reference statements)
2
2
0
Order By: Relevance
“…The results show a good agreement between the simulated and measured flow velocities, except near the casing wall at x=L = 1 where the CFD simulation over-predicts velocity magnitudes. A similar local discrepancy at the S-duct exit was also observed by Milanovic et al (2014), albeit on a strutted version of the baseline model; they attributed it to the shortcomings of the turbulence models. Note that, in the absence of error statistics for the measurements (Britchford et al, 1994;Britchford, 1998), the significance of this local discrepancy between the simulated values and the reported measurements cannot be quantified.…”
Section: Model Validation 331 Simulationsupporting
confidence: 70%
See 1 more Smart Citation
“…The results show a good agreement between the simulated and measured flow velocities, except near the casing wall at x=L = 1 where the CFD simulation over-predicts velocity magnitudes. A similar local discrepancy at the S-duct exit was also observed by Milanovic et al (2014), albeit on a strutted version of the baseline model; they attributed it to the shortcomings of the turbulence models. Note that, in the absence of error statistics for the measurements (Britchford et al, 1994;Britchford, 1998), the significance of this local discrepancy between the simulated values and the reported measurements cannot be quantified.…”
Section: Model Validation 331 Simulationsupporting
confidence: 70%
“…In this context, Britchford et al (1994) compared the k-e turbulence model and the Reynolds stress model, and reported that the mean velocity profile and shear stress are predicted better by the latter. Milanovic et al (2014) carried out RANS simulations for detailed sensitivity analysis of strutted compressor ducts, with the k-v and Spalart-Almaras turbulence models. Their computational predictions indicated good agreement with experimental data.…”
Section: Boundary Conditions and Submodel Selectionmentioning
confidence: 99%
“…3a, and it could be understood that excluding small discrepancies near to both walls, predicted simulation and experimental results matched quite well. However, similar discrepancies were also reported by the Milanvoic et al and Immonen [40,42] because of the improper handling of the wall curvature by the turbulence model. Duenas [15] had also commented that it might be difficult the accurate prediction of flow under the highly curved wall surface by Boussinesq eddy-viscosity turbulence models.…”
Section: Numerical Methods Validationsupporting
confidence: 78%
“…The loss coefficient increased from 0.040 to 0.042 for without compressor case whereas it increased from 0.035 to 0.038 with compressor case. Milanovic et al [43] Baloni et al [44] One, six and eight strut -Computational fluid dynamics showed the capability to capture the flow physics of the duct accurately under the strutted environment. -Similar to the experimental study, numerical simulation also captured wakes near to the trailing edge of the strut.…”
Section: Number Of Struts Remarkmentioning
confidence: 99%